2018
DOI: 10.33240/rba.v13i5.22750
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade Fisiológica De Sementes Crioulas De Milho Pipoca

Abstract: Estudou-se a qualidade fisiológica de genótipos crioulos de milho pipoca amarelo, vermelho e preto, oriundos de guardião de sementes da agricultura familiar do sudoeste do Paraná. Avaliou-se germinação, vigor de sementes e de plântulas. Todos os genótipos de milho pipoca analisados possuem germinação e vigor adequados para a sua propagação na forma de semente. O genótipo de milho pipoca vermelho possui germinação e vigor superiores aos genótipos amarelo e preto.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…The same result was observed by Stefanello (2014) with the seeds of native maize varieties subjected to different periods and storage conditions. Rodrigues et al (2018) observed that the red genotype of landrace popcorn stood out from the others, with an average germination rate of 94%, similar to that obtained in this study. The high germination test results do not necessarily mean that the seeds have high vigor, considering that the germination test is carried out under favorable environmental conditions of temperature, humidity, and light, allowing the expression of the maximum potential for the production of normal seedlings (Marcos Filho, 1999).…”
Section: Physiological Properties Of the Lpsupporting
confidence: 89%
“…The same result was observed by Stefanello (2014) with the seeds of native maize varieties subjected to different periods and storage conditions. Rodrigues et al (2018) observed that the red genotype of landrace popcorn stood out from the others, with an average germination rate of 94%, similar to that obtained in this study. The high germination test results do not necessarily mean that the seeds have high vigor, considering that the germination test is carried out under favorable environmental conditions of temperature, humidity, and light, allowing the expression of the maximum potential for the production of normal seedlings (Marcos Filho, 1999).…”
Section: Physiological Properties Of the Lpsupporting
confidence: 89%